Exploring the Intersections of Literary Theory and Cultural Studies - Jain, Anuj (Journal of Advanced Research in English & Education; Vol 8 No 3 (2023): Journal of Advanced Research in English & Education, 2023)
This comprehensive review examines the intricate relationship between literary theory and cultural studies, unraveling their historical evolution, key theoretical frameworks, and contemporary applications. Tracing the roots to the mid-20th century, we explore how literary theory and cultural studies emerged as transformative approaches to understanding literature within broader cultural contexts. Structuralism, poststructuralism, postcolonial theory, feminist theory, and queer theory are dissected as pivotal frameworks that have shaped discourse, challenging conventional interpretations and fostering a deeper understanding of cultural nuances. Delving into contemporary applications, the review investigates how scholars employ these frameworks to analyze diverse cultural products, from traditional literature to digital media. The impact of global literature and transnational cultural flows is discussed, emphasizing the need for inclusive perspectives. Furthermore, the influence of digital technologies on literature and culture is explored, unraveling the transformative effects on production, distribution, and reception. As the dynamic interplay between literature and culture continues to evolve, scholars are prompted to adapt their analytical tools. This review underscores the importance of fostering a continued dialogue between literary theory and cultural studies, acknowledging their symbiotic relationship as indispensable lenses for enriching our understanding of the ever-evolving human expression.